2002
DOI: 10.1002/1439-7641(20020916)3:9<795::aid-cphc795>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Anodic Work Function on the Performance of Organic Solar Cells

Abstract: Cutting etch organic solar cells utilize the bulk‐heterojunction concept, shown in the graphic, of interpenetrating electron and hole conducting networks which enhances the exciton splitting process in the photosensitive layer. Generated charges are turned into current due to the built‐in field given by the adjoining electrodes. Here, the influence of an altered doping level of the hole collecting electrode has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 12 publications
4
120
2
Order By: Relevance
“…12 On the other hand, electrochemical modification of the PEDOT work function in PPV-based solar cells showed that the opencircuit voltage exactly followed the behavior as expected from the PEDOT work function. 13 This shows that the PE-DOT work function is not pinned in this system, which supports our estimate of the hole density at the interface. We use a recently developed drift-diffusion model to calculate the distribution of holes p͑x͒ as a function of distance x in the device.…”
Section: ͑1͒supporting
confidence: 83%
“…12 On the other hand, electrochemical modification of the PEDOT work function in PPV-based solar cells showed that the opencircuit voltage exactly followed the behavior as expected from the PEDOT work function. 13 This shows that the PE-DOT work function is not pinned in this system, which supports our estimate of the hole density at the interface. We use a recently developed drift-diffusion model to calculate the distribution of holes p͑x͒ as a function of distance x in the device.…”
Section: ͑1͒supporting
confidence: 83%
“…In addition, the oxidation potential E ox of a PEDOT:PSS lm was measured using CV. 47 We assume that E ox of PEDOT:PSS measured using CV is equivalent to F measured using UPS and equate a linear scale between CV and UPS with PEDOT:PSS as the reference point. All other electrochemical states measured using CV from other polymers are referenced to this.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Frohne and coworkers systematically modified the work function of PEDOT:PSS films electrochemically [50,51]. The treatment of electrically polymerized PEDOT film in the presence of sodium-neutralized PSS resulted in PEDOT:PSS films with work function variations up to 1.3 eV, depending on the doping level.…”
Section: Figurementioning
confidence: 99%
“…The PEDOT:PSS film was then incorporated into poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1,4-phenylenevinylene] (MDMO-PPV)/[6,6]-phenyl-fullerene-butyric acid methyl ester (PCBM) solar cells as the hole-transporting layer, and the compensation voltage, V0 (V0 is the potential at which the photocurrent equals the dark current, which is proportional to the Voc) tracks the work function of PEDOT:PSS. However, as the work function of PEDOT:PSS is beyond 0.3 V versus Ag/AgCl, the Vo plateaus [51]. Later, Li and coworkers found that the photovoltaic performance of poly(3-hexylthiophene) (P3HT):PCBM solar cells can be improved by incorporating a PEDOT:PSS IFL between the indium tin oxide (ITO) and the active layer [52].…”
Section: Figurementioning
confidence: 99%